(untitled) (Orthodontic Journal of Nepal, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is a contagious disease caused by severe acute respiratory syndrome coronavirus 2 . The aim of this study was to assess the knowledge, attitude and practice related to COVID-19 among dental patients visiting Pokhara Academy of Health Sciences, Pokhara. Materials and Method: The cross-sectional study was carried out in the dental patients visiting Pokhara Academy of Health Sciences, Pokhara. Convenient sampling was used. A structured questionnaire was organized into four different sections: section I, section II, section III and section IV which contained socio-demographic information, knowledge, attitude and practice towards universal safety precautions of Covid-19 respectively. Descriptive statistics including mean, standard deviation, median, interquartile range, proportion were calculated along with tabulation presentation. ANOVA and T Tests were used wherever necessary. Result: The mean age of the participants was 35.53 ± 14.24, ranging from 18 to 73 years. Mean knowledge of Covid-19 of the participants was found to be 7.23±1.88. Almost 73.5% of the participants didn’t go outside during Covid-19 pandemic, 86% of the participants wore surgical mask/N-95 mask while going outside, 90.5% of the participants maintained minimum physical distance of 2 meters between two or more people, and 89% of the participants used sanitizer or washed their hands after touching any surfaces. Almost all the participants (96.5%) advised a person visiting from abroad or high Covid-19 cases area to stay in quarantine for more than 10 days. There was statistically significant relationship of mean knowledge with age, marital status, education, occupation and monthly income (p≤0.05). Conclusion: Majority of the participants had good level of knowledge on COVID-19, positive attitude towards all preventive measures and good practice related to COVID-19 infection.